Neoantimycin F, a Streptomyces-Derived Natural Product Induces Mitochondria-Related Apoptotic Death in Human Non-Small Cell Lung Cancer Cells - Liu, Liyun; Zhu, Hongrui; Wu, Wei; Shen, Yaoyao; Lin, Xiao; Wu, Ying; Liu, Li; Tang, Jie; Zhou, Yongjun; Sun, Fan; Lin, Hou-Wen (Frontiers in Pharmacology, 2019)
Streptomyces-derived natural products have been become a major focus of anti-tumor drug discovery studies. Neoantimycin F (NAT-F), was isolated from Streptomyces conglobatus by our group. Here, we examined the anti-cancer activities and its underlying molecular mechanisms implicated in NAT-F–induced apoptosis of non–small cell lung cancer (NSCLC) cells. Our results showed that NAT-F exerted excellent growth-inhibitory activity against PC9 and H1299 cells in a concentration-dependent manner. NAT-F–induced cell cycle arrest at S and G0/G1 phase in PC9 and H1299 cells, respectively. Further investigation revealed that the key proteins (including cyclinD1, cyclinE1, cyclinB1, CDK2, and CDK4) were involved in the cell regulation by NAT-F. Additionally, NAT-F significantly increased the production of reactive oxygen species (ROS), induced DNA damage, nuclear condensation, and cell apoptosis in both cell lines. Moreover, loss of the mitochondrial membrane potential (MMP) was markedly induced by NAT-F. Additional results revealed that NAT-F could up-regulate pro-apoptotic protein Bax and down-regulate anti-apoptotic protein Bcl-2, Mcl-1, and Bcl-xL, resulting in cytochrome c release from mitochondria and sequential activation of caspase-9 and -3, as well as the cleavage of poly (ADP-ribose) polymerase. Meanwhile, c-Jun N-terminal kinase (JNK), p38 MAPK (p38), and extracellular signal-regulated kinase (ERK) signaling pathway were also involved in anti-cancer activity of NAT-F in NSCLC cells. Taken together, these findings indicated that NAT-F possessed anti-proliferative effect and induced apoptosis in NSCLC cells in vitro and may be conducive to promote the development of novel anti-NSCLC agents.